Essays on the History of Mechanics
256 p.
Keywords: The history of mechanics, and more particularly, the history of mechanics applied to constructions, constitutes a field of research that is relatively recent. This volume, together with the recent publication "Towards a History of Construction", is intended as an homage to the two eminent scholars who made a determinant contribution to the history of mechanics: Edoardo Benvenuto and Clifford Truesdell.